2019
DOI: 10.31223/osf.io/epa9m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analog forecasting of extreme-causing weather patterns using deep learning

Abstract: Numerical weather prediction (NWP) models require ever-growing computing time/resources, but still, have difficulties with predicting weather extremes. Here we introduce a data-driven framework that is based on analog forecasting (prediction using past similar patterns) and employs a novel deep learning pattern-recognition technique (capsule neural networks, CapsNets) and impact-based auto-labeling strategy. CapsNets are trained on mid-tropospheric large-scale circulation patterns (Z500) labeled $0-4$ dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…The same structure is used for all models within each class, as shown in Table 1. These combinations of layers and dimensions are similar to prior studies using deep learning with weather data for different applications over similar‐sized domains (Chattopadhyay et al., 2020; Chapman et al., 2019; Larraondo et al., 2019). In general, preliminary experiments suggest that model performance for higher lead times and quantiles tends to improve with more layers and parameters, though with increased risk of overfitting, which occurs when an increase in model complexity reduces performance on the test data.…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…The same structure is used for all models within each class, as shown in Table 1. These combinations of layers and dimensions are similar to prior studies using deep learning with weather data for different applications over similar‐sized domains (Chattopadhyay et al., 2020; Chapman et al., 2019; Larraondo et al., 2019). In general, preliminary experiments suggest that model performance for higher lead times and quantiles tends to improve with more layers and parameters, though with increased risk of overfitting, which occurs when an increase in model complexity reduces performance on the test data.…”
Section: Methodssupporting
confidence: 73%
“…Prediction tasks with image inputs are typically addressed with convolutional neural networks (CNNs), because they can detect patterns across scales, shapes, and locations relevant for prediction (Schultz et al., 2021). Recent studies have focused on advancing CNNs and other DL models that learn directly from spatial data, rather than manually extracted features (e.g., Chattopadhyay et al., 2020; Liu et al., 2016). Many of these efforts have centered around short‐term precipitation forecasting or nowcasting experiments (Castro et al., 2021; Hernández et al., 2016; Larraondo et al., 2019; Shi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The cluster patterns are obtained by minimizing the Euclidian distance between iteratively updated cluster's pattern and their matching daily Z500 anomaly fields. It should be mentioned that there are a variety of methods that have been used for clustering weather patterns and it is not clear if any is better than the rest (e.g., see Ashok et al., 2017; Chattopadhyay, Hassanzadeh, & Pasha, 2020; Ghil & Robertson, 2002; Mo & Ghil, 1988; Robertson & Mechoso, 2003; Sahai et al., 2017; Straus, 2018). At least one recent study (Bao & Wallace, 2015) concluded that the flow regimes derived from SOM analysis are more distinctive and more robust than those obtained using Ward's method, which is a type of hierarchical clustering technique.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, CWS has been broadly applied in weather forecasts and statistical climatology. In ensemble forecasts, CWS is utilized to generate a set of pre‐defined circulation types and simplify the ensemble forecasts, where each weather pattern of ensemble members is assigned to the closest matching type, to a sequence of circulation type probabilities (Chattopadhyay et al., 2020; Neal et al., 2016; Ohba et al., 2018), hence reducing computational complexity while maximizing useful information. In climatology, classification helps examine climate‐scale changes in the frequency of circulation types (Gibson et al., 2016; Luong et al., 2020; Lynch et al., 2006).…”
Section: Introductionmentioning
confidence: 99%